Collected stories - García Márquez, Gabriel
Sweeping through crumbling towns, travelling fairs and windswept ports, Gabriel Garcia Marquez introduces a host of extraordinary characters and communities in his mesmerizing tales of everyday life: smugglers, bagpipers, the President and Pope at the funeral of Macondo's revered matriarch; a every old angel with enormous wings, stranded in a young couple's back garden; a town plagued by dying birds that fall from the sky and an awestruck village captivated by a beautiful drowned sailor. Teeming with the magical oddities for which his novels are loved, Marquez's stories are a delight